Ultrasound Molecular Imaging as a Potential Non-invasive Diagnosis to Detect the Margin of Hepatocarcinoma via CSF-1R Targeting - Jiang, Qiongchao; Zeng, Yunting; Xu, Yanni; Xiao, Xiaoyun; Liu, Hejun; Zhou, Boyang; Kong, Yao; Saw, Phei Er; Luo, Baoming (Frontiers in Bioengineering and Biotechnology, 2020)
Though radiofrequency ablation (RFA) is considered to be an effective treatment for hepatocellular carcinoma (HCC), but more than 30% of patients may suffer insufficient RFA (IRFA), which can promote more aggressive of the residual tumor. One possible method to counter this is to accurately identify the margin of the HCC. CSF-1R has been found to be restrictively expressed by tumor associated macrophages (TAMs) and monocytes which more prefer to locate at the boundary of HCC. Using biotinylation method, we developed a CSF-1R-conjugated nanobubble CSF-1R (NBCSF-1R) using a thin-film hydration method for margin detection of HCC. CSF-1R expression was higher in macrophages than in HCC cell lines. Furthermore, immunofluorescence showed that CSF-1R were largely located in the margin of xenograft tumor and IFRA models. In vitro, NBCSF-1R was stable and provided a clear ultrasound image even after being stored for 6 months. In co-culture, NBCSF-1R adhered to macrophages significantly better than HCC cells (p<0.05). In in vivo contrast-enhanced ultrasound imaging, the washout half-time of the NBCSF-1R was significantly greater than that of NBCTRL and Sonovue® (p<0.05). The signal intensity of the tumor periphery was higher than the tumor center or non-tumor region after NBCSF-1R injection. Taken together, NBCSF-1R may potentially be used as a non-invasive diagnostic modality in the margin detection of HCC, thereby improving the efficiency of RFA. This platform may also serve as a complement method to detect residual HCC after RFA; and may also be used for targeted delivery of therapeutic drugs or genes.